Effects of dry fog humidification on pericarp browning and quality of litchi fruit stored at low temperature - Xiao, Lu; Li, Taotao; Jiang, Guoxiang; John, Afiya; Zhang, Dandan; Jin, Wenyuan; Duan, Xuewu; Jiang, Yueming (International Journal of Agricultural and Biological Engineering, 2019)
Pericarp browning is the major cause of deterioration of harvested litchi fruit. Water loss plays a role in pericarp browning of litchi fruit. This study investigated the effects of humidification with dry fog on pericarp browning and quality of litchi fruit stored at low temperature. Litchi fruit were stored in a non-humidified cold chamber (control) or in a humidified cold room using Tabor atomizer system that generated 95% relative humidity (RH) without depositing water on the fruit surface at 4°C. Control fruit stored in cold room without added humidity underwent rapid weight loss, accompanied by severe pericarp browning after 25 d of storage. However, slight weight loss and no obvious pericarp browning were found in humidified-fruit. Moreover, humidification maintained well the integrity of cell membrane and inhibited polyphenol oxidase activity during early storage. In addition, respiration rate was obviously inhibited in humidified-fruit compared with control fruit. This study might provide a convenient approach to reduce pericarp browning of harvested litchi fruit by humidifying the fruit using the Tabor atomizer at low temperature instead of packaging with film. Keywords: litchi, pericarp browning, dry fog, high relative humidity, cold storage DOI: 10.25165/j.ijabe.20191204.4420 Citation: Xiao L, Li T T, Jiang G X, John A, Zhang D D, Jin W Y, et al. Effects of dry fog humidification on pericarp browning and quality of litchi fruit stored at low temperature. Int J Agric & Biol Eng, 2019; 12(4): 192–196.